Metode Desain Karakter Aaron Blaise dengan Penerapan Antropomorfisme dalam Animasi Lakontara sebagai Upaya Pelestarian Ketoprak - Aroisi, Nawawel Sakti; Kurniawan, Rendya Adi (CITRAWIRA : Journal of Advertising and Visual Communication, 2023)
The Marmalade team with their animation titled "Lakontara" has successfully won a gold medal in the GEMASTIK XV 2022 event. In their animation, Marmalade raises the issue of the low interest of the community in traditional Javanese theater (ketoprak) performances, and how ketoprak can remain relevant and compete with other modern entertainments. In the character design of Lakontara, it can be seen that the characters are predominantly non-human characters given human attributes and behaviors, indicating that the characters are designed using anthropomorphism. This is commonly found in popular animations such as Cars, Toy Story, and SpongeBob SquarePants. Anthropomorphism is claimed to make animations appear funnier and more appealing because it can bring something impossible in the real world into the animation.